Burnout and wellbeing of teacher candidates: The mediator role of cynicism - Bakioğlu, Fuad; Kiraz, Zafer (Anales de Psicología / Annals of Psychology, 2019)
The aim of this study was to investigate a mediator role of cynicism in the relationship between burnout and wellbeing. Participants were 326 teacher candidates [189 (58%) female, 137 (42%) male, Mage = 23.14 years, SD = 2.36] who completed questionnaires package the Burnout Measure Short Version, the Positive and Negative Affect Schedule, Life with Satisfaction Scale and the Hunter Cynicism Scale. The data were analyzed using structural equation modeling. A bootstrapping analysis was conducted in order to determine any indirect effects. The results showed that burnout predicted cynicism positively and wellbeing negatively, and that cynicism predicted wellbeing negatively. It was further found that the structural equation model that proposed that burnout had a direct and an indirect effect through cynicism on wellbeing was confirmed. The results of the study were discussed in the light of relevant literature, and suggestions for future studies were made.